Level of knowledge on zakat among residents at Wilayah Persekutuan - Nor Syarifah Syahirah Andry; Noraishah Salim; Norfazlinie Mahadi; Norlaina Nordin (2023)
This study identifies the level of knowledge on zakat among residents at the WilayahnPersekutuan in learning Baitul Mal knowledge, 8 Asnaf knowledge, zakat centre, zakat calculation and the obligation to pay zakat. The independent variable of this study consists of knowledge about Baitul Mal, the knowledge of 8 aAsnaf, zakat centre, zakat calculation and the obligation to pay zakat while the dependent variable in this study is the level of knowledge among residents at the Wilayah Persekutuan. Therefore, in this study the theory used is the Theory of Planned Behavior (TPB), this is used to see the extent of the zakat knowledge of the people of theWilayah Persekutuan of the studied zakat sciences. The quantitative research method is used as a research instrument to collect data with prepare survey questions that are built using google form. This study uses non-probability sampling. Respondents will be selected using a convenience sample approach in this analysis, which will use non-probability sampling. Sampling is convenient, as participants are selected based on their proximity to sampling location. The data collected was analysed using software based on Statistical Packages for Social Science Version 29 (SPSS Version 29) to analyse descriptive statistics, reliability analysis, and Spearman correlation analysis.Based on the results of the study, found that the knowledge of baitulmal among residents of the Wilayah Persekutuan is known where the majority of respondents scale likert 4. The highest frequency for the Asnaf group is Poor with a frequency of 239 respondents followed by Fakir which is 236 respondents on a likert scale of 5. After that, knowledge of the calculation of Zakat, respondents chose scale Likert 5, with the results showing a positive relationship that proves among residents at the Wilayah Persekutuan know how to calculate zakat on livestock. This study found that the knowledge of Baitul Mal among residents at the Wilayah Persekutuan is known where the majority of respondents scale likert 4. In addition, the study also found that the knowledge of the zakat center among residents at the Wilayah Persekutuan shows the results of the majority on the likert scale 4. or the knowledge of the obligation to pay zakat, respondents chose scale likert 5, with the results, showing a positive relationship that proves that residents at Wilayah Persekutuan know Islam is a mandatory condition to pay zakat. Regarding the results, all independent variables (Baitulmal knowledge, science 8 asnaf, zakat centre, calculation zakat and the obligation to pay zakat) studied in this research has a relationship with the dependent variable (level of knowledge among residents at the Wilayah Persekutuan) in understanding zakat. Through this study, we will understand the level of knowledge on zakat among residents at the Wilayah Persekutuan.